Moderate‐severe primary graft dysfunction after pediatric heart transplantation. (4th January 2019) - Mowers, Katie L.; Simpson, Kathleen E.; Gazit, Avihu Z.; Eghtesady, Pirooz; Canter, Charles E.; Castleberry, Chesney D.
Abstract: Background: PGD is a complication after heart transplantation (OHT) and a significant cause of mortality, particularly in infant recipients. Lack of standardized definition of PGD in the pediatric population makes the prevalence and magnitude of impact unclear. Methods: ISHLT PGD consensus guidelines, which include inotrope scores and need for MCS, were applied retrospectively to 208 pediatric OHT recipients from a single institution from 1/2005‐5/2016. PGD was defined as: moderate PGD—inotrope score >10 on postoperative day 1 (24‐48 hours), and severe PGD—MCS within 24 hours (in the absence of detectable rejection). Results: PGD occurred in 34 patients (16.3%); 14 of which had severe PGD (6.7%). Multivariate risk factors for PGD included CPB time (OR 10.3/10 min, 95% 10.05, 10.2, P = 0.03), Fontan palliation (OR 1.9, 95% 1.2, 3.97), and PCM (OR 5.65, 95% 1.52, 22.4); but not age, weight, ischemic time, or donor characteristics. Upon sub‐analysis excluding patients with PCM, increased CPB was a significant multivariate risk factor (OR 10.09, 95% 9.89, 10.12, P = 0.003). Patients with PGD had decreased discharge survival compared to those without PGD (85% vs 96%, P < 0.01). Severe PGD was associated with the poorest 1‐year survival (57% vs 91% without PGD, P = 0.04). Conclusion: Patients with prolonged CPB are potentially at risk for developing PGD. Neither infant recipients nor donor characteristics were associated with an increased risk of PGD in the current era.